Money-oriented risk-takers or deliberate decision-makers: a cross-sectional survey study of participants in controlled human infection trials - Marie-Astrid Hoogerwerf; Martine de Vries; Meta Roestenberg (BMJ Open)
Objective To quantitatively investigate the motivations, decision-making and experience of participants in controlled human infection (CHI) studies.Design Cross-sectional descriptive survey study.Setting Previous participants of CHI studies at the Leiden Controlled Human Infection Center, control group of students from Leiden University.Participants 61 previous participants and 156 controls.Measurements Ranking of motivational and decisional factors, risk propensity score and multiple-choice questions on experience of trial participation and ethical aspects of CHI studies.Results Motivating factors for participants were contributing to science (81%), contributing to research that may benefit developing countries (72%) and the financial compensation (63%). For 51% of participants, a reason other than financial compensation was the most important motivational factor. Participants considered trust in the study team (70%), time investment (63%), severity of symptoms (54%), chance of developing symptoms (54%) and whether it is an easy way to make money (54%) in their decision to participate. Most CHI participants (84%) were proud of their participation, would advise others to participate (89%) and would participate in a similar trial again (85%). CHI participants had a higher risk propensity score than students (estimated difference 0.9, p<0.001).Conclusion Although financial compensation is important, the motivations for participants in a CHI study are diverse and participants make a balanced appraisal of risks and burden before participating.